Perceived stressors of oral hygiene students in the dental environment - Chrisleen Rayner; Natalie Gordon; Vivienne Wilson; Kariema Crombie; Amenah Shaikh; Soraya Yasin-Harnekar (South African Medical Association, 2016)
Background. University students are exposed to a multitude of stressors that may impact on their performance. The nature of health sciences education generally involves early engagement with patients and communities, which may add to the stressors inherent to university life. There is sparse information on stressors in the oral hygiene educational environment. Objective. To determine perceived stressors and the level of burnout among oral hygiene students at the University of the Western Cape, Cape Town, South Africa. Method. A descriptive, cross-sectional study design was used. The study sample included all students in the Bachelor of Oral Health (BOH) degree during 2012 (N=89). A self-administered questionnaire was used to gather data. Three parameters were measured, i.e. (i) demographic characteristics; (ii) perceived sources of stress, using a modified Dental Environment Stress (DES) questionnaire; and (iii) burnout, using the Maslach Burnout Inventory (MBI). Results. Respondents were mostly female (74%) and primarily in the 18 - 25-year age group (92%). First- and 2nd-year students identified fear of failing and study load as major stressors. Stressors related to a lack of basic needs were identified as major stressors by 25% of 1st-year students. Third-year students identified clinical quotas, supervision and patients being late as major stressors. MBI scores indicated that students were not at risk for burnout; however, most students (66.2%) scored high on emotional exhaustion (EE). Conclusion. Oral hygiene students identified stressors in their learning environment. There was a progressive increase in EE across academic years. The results suggest that interventions should be tailored for specific academic year groups.